2008
DOI: 10.1002/jcu.20442
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic diagnosis of spontaneous intramural small bowel hematoma in a case of warfarin overdose

Abstract: A 38-year-old man who had been treated with warfarin since mitral valve replacement 10 years earlier presented with acute onset of epigastralgia and melena. Coagulation tests were abnormal with a prolonged prothrombin time of >60 seconds and a prolonged activated partial thromboplastin time of >120 seconds. Abdominal sonographic examination revealed duodenal intramural hematoma that was confirmed on CT. Warfarin therapy was stopped and the patient was treated conservatively with vitamin K and fresh frozen plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 5 publications
0
17
0
6
Order By: Relevance
“…Intestinal intramural hematoma is located in the duodenum especially in children, whereas spontaneous intramural hematoma is often seen in the jejunum. Hemorrhagic complications of anticoagulant medications are hematuria, gastrointestinal hemorrhage, intracerebral hemorrhage, soft tissue hematoma, epistaxis, and retroperitoneal hematomas (1). Bleeding as intramural hematoma of the small intestine is rare, seen in 1 out of 2500 patients (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal intramural hematoma is located in the duodenum especially in children, whereas spontaneous intramural hematoma is often seen in the jejunum. Hemorrhagic complications of anticoagulant medications are hematuria, gastrointestinal hemorrhage, intracerebral hemorrhage, soft tissue hematoma, epistaxis, and retroperitoneal hematomas (1). Bleeding as intramural hematoma of the small intestine is rare, seen in 1 out of 2500 patients (2).…”
Section: Introductionmentioning
confidence: 99%
“…Other risk factors are hemobilia, idiopathic thrombocytopenic purpura, leukemia, lymphoma, myeloma, chemotherapy, vasculitis, pancreatitis, and pancreatic cancer (3,4). Conditions requiring surgery are serious intraluminal bleeding, bowel perforation or the presence of ischemia (1,2). If diagnosis can be confirmed, conservative treatment with correction of coagulation parameters is satisfactory in most cases (5).…”
Section: Introductionmentioning
confidence: 99%
“…Intra-peritoneal hemorrhagic effusion, when present, is related to the leakage of blood from an enlarged, thickened and inflamed bowel wall with submucosal bleeding into all layers [3][4][5]. Clinical presentation can vary from mild, vague abdominal pain to intestinal obstruction and an acute abdomen [6,7]. Our patient displayed an acute abdomen with widespread abdominal defense.…”
Section: Discussionmentioning
confidence: 80%
“…9 In a study, Abdel Samie and Theilman reported a case of intramural hematoma in four patients who received an anticoagulant (phenprocoumon) due to atrial fibrillation. Of these, 2 were localized in the jejunum, whereas 1 in the duodenum and 1 in the rectum.…”
Section: Referencesmentioning
confidence: 99%